Clinicopathological parameters of oral squamous cell carcinoma in Florianópolis: A 10-year study - Martini, Georgia; Los-Santos, Gustavo de; Bordignon, Natalia; Girardi, Carla; Mariano, Fernanda Viviane; Daniel, Filipe Ivan; Gondak, Rogério Oliveira (Journal of Oral Diagnosis, 2019)
Oral squamous cell carcinoma (OSCC) is one of the most common cancers and presents the highest mortality rate of head and neck tumours. The aim of this study was to eva- luate the clinical and histological features of patients with OSCC in Florianópolis, Santa Catarina, Brazil between 2006 and 2016. Demographic and clinical characteristics such as age, gender, tobacco and alcohol consumption, anatomical site, clinical stage, and tre- atment were retrospectively collected from histopathological and medical reports. Of 196 patients with OSCC, 82.14% were male with a mean age of 58.28±10.45 years. Tobacco and alcohol consumption was reported in 88.76% and 75.9% of patients, respectively. The tongue was the anatomical site most affected (25.13%) and ulcers were the most prevalent clinical aspect (95.21%). A total of 103 (52.55%) patients were diagnosed with advanced stage (III/IV). Regarding treatment, 59.24% received more than one type of therapy, while 39.67% were treated exclusively with surgery. Regarding histological differentiation, 72.9% of the cases were moderately/poorly differentiated, 23.8% had vascular invasion, 17.9% had lymphatic invasion, and perineural invasion was observed in 29.5% of the patients. The survival rate showed a worse prognosis for patients diagnosed at stage III/ IV and the primary tumour was located in the inferior level of the mouth in 80% of these cases. The results showed that the majority of cases were diagnosed at an advanced stage, compromising treatment and prognosis. Educational and preventive measures should be improved in an effort to allow for early diagnosis.